A Behavioral Design to Reform Italy's Evaluation Policy. (December 2021) - Marra, Mita
Drawing on the extensive ethnographic research I conducted on Italy's performance evaluation system, this article highlights the cognitive biases associated with evidence use in decision making and institution working. Framing effects, status quo bias, motivated reasoning, and tacit conflicts between personal and organizational interests were only some of the behavioral phenomena policy makers, managers, and evaluators showed to limit their exposure to performance information. Integrating behavioral findings with theories of governance, evaluation utilization, and critical evidence–informed policymaking, this article discusses behavioral reform strategies to overcome (i) tacit conflicts of interests among evaluators, (ii) the compliance mentality with performance assessment among managers, and (iii) adversarial relationships between courts and administrative agencies as well as polarized politics with respect to evidence use and experts' behavior. A behavioral design is relevant to reform evaluation policies, especially in countries where performance regimes have been criticized, contested, resisted, and/or perceived as red tape and surveillance mechanisms.